2019
DOI: 10.1192/bjo.2018.80
|View full text |Cite
|
Sign up to set email alerts
|

Associations between childhood maltreatment and inflammatory markers

Abstract: BackgroundChildhood maltreatment is one of the strongest predictors of adulthood depression and alterations to circulating levels of inflammatory markers is one putative mechanism mediating risk or resilience.AimsTo determine the effects of childhood maltreatment on circulating levels of 41 inflammatory markers in healthy individuals and those with a major depressive disorder (MDD) diagnosis.MethodWe investigated the association of childhood maltreatment with levels of 41 inflammatory markers in two groups, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…Informed written consent was obtained from all participants at the time of sample collection. The 35 inflammatory markers represent adequately expressed cytokines from an initial panel of 42, which were originally assayed in relation to major depression risk, as described previously 48 . The mean age of our sample was 48.7 ± 15.1 (standard deviation), with a mean body mass index of 27.3 ± 5.5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Informed written consent was obtained from all participants at the time of sample collection. The 35 inflammatory markers represent adequately expressed cytokines from an initial panel of 42, which were originally assayed in relation to major depression risk, as described previously 48 . The mean age of our sample was 48.7 ± 15.1 (standard deviation), with a mean body mass index of 27.3 ± 5.5.…”
Section: Methodsmentioning
confidence: 99%
“…The first phase aimed to assess common physical and mental disorders in South East London; the second, to examine the roles of historical social context and policy in shaping patterns of health inequalities; and the third, to collect biological specimens from a subset of participants, including blood for serum separation and DNA for genotyping. Serum and DNA were extracted and stored at −80 °C until use, as described previously 47,48 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the tools guidelines studies can be categorised as low quality (<20), moderate quality (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and high quality (30+). All papers were rated by 1 reviewer, and the 2 nd reviewer independently quality rated a sub-sample of 25% of papers.…”
Section: Methods Of Reviewmentioning
confidence: 99%
“…BMI-Body mass index, CM-Child Maltreatment, CRP-C-reactive protein, CTQ-Childhood Trauma Questionnaire, EA-Emotional abuse, EN-Emotional neglect, ETI-Early Trauma Inventory, FEP-First Episode Psychosis, MDD-Major Depressive Disorder, PA-Physical abuse, PN-Physical abuse, SA-Sexual abuse, UHR-Ultra-high riskAll papers reporting clinical samples were retrospective and all but one used CTQ to record CM. Four studies did not find any association between CM and CRP[24][25][26][27]. A further two studies found initially significant associations between CM measures and CRP, which attenuated to non-significance on adjustment for BMI[28,29].…”
mentioning
confidence: 99%